An Optical Cluster: Near‐Field Optical Sorting and Separation of Plasmonic, Dielectric, and Chiral Nanoparticle. Issue 10 (27th August 2021) - Das, Saikat Chandra; Mahdy, Mahdy Rahman Chowdhury; Islam, Md Shariful; Jani, Rafsan; Bhuiyan, Md Shahadat
Abstract: Separating distinct nanoparticles from a cluster by applying simple nonstructured light can be a novel approach for future industrial development. Understanding the type of distinct particles from a three‐particle cluster (i.e., chiral, plasmonic, and dielectric) based on different near‐field optical forces has not been reported so far. In most of the set ups, optical sorting is reported for radius‐based sorting of Mie‐ranged single object. Here, three different optical setups are proposed, illuminated by a linearly polarized plane wave (propagating along θ = 45 ∘ angle) in a particle cluster constructed with chiral, plasmonic, and dielectric nanoparticles in an air medium (case 1), half immersed in water (case 2), and fully immersed in water (case 3). All of those have supported the near‐field optical sorting from the cluster of three Rayleigh sized particles. It is observed that the dielectric object experiences counter‐intuitive optical pulling force mainly due to the effect of induced magnetic‐type resonance created on nearby plasmonic object. In contrast, plasmonic objects experience optical pushing force due to the transferred momentum of photon and chiral objects experience lateral force mainly due to the induced magnetic dipole on the chiral object. Abstract : The optical‐force‐based sorting and separation of dielectric (experienced pulling force), plasmonic (pushing force), and chiral (lateral force) Rayleigh‐sized nanoparticles from a cluster or mixture illuminated by a simple plane wave is proposed. Such all‐optical sorting by using light beams may open a new way of separating nanoparticles from a mixture without using traditional or costly chemicals.